Differential expression of α6 and β1 integrins reveals epidermal heterogeneity at single‐cell resolution. Issue 3 (3rd November 2019) - He, Weiya; Ye, Jinguo; Xu, Huiyi; Lin, Yangsheng; Zheng, Yingfeng
Abstract: Skin epidermis is a constantly renewing epithelium that is composed of various cell types and provides an ideal model system for tissue regeneration and heterogeneity studies. Integrins are a family of transmembrane receptors that mediate cell adhesion in the epidermis, and integrin expression spatially reflects epidermal heterogeneity. It remains unclear whether differential expression of integrins can characterize cell types in skin epidermis. This study applied a fluorescence‐activated cell sorting (FACS) strategy based on differential expression of α6 and β1 integrins, and used transcriptome analysis to explore epidermal heterogeneity. First, epidermal cells were acquired from C57BL/6 mice back skin. Nine bulk‐cell populations were sorted with differential expressions of α6 and β1 integrins, and were successfully characterized as the main cell types in the epidermis through RNA‐seq and transcriptome analysis. Then, tetOKrt14‐H2BGFP mice were used to trace the cell proliferation rate during wound healing with GFP intensity. Epidermal cells were acquired from the re‐epithelialized back skin wounds, and a total of 576 single cells were sorted, combining integrin expression and GFP tracing. FACS single‐cell RNA‐seq enabled high resolution in the classification of subtypes in both interfollicular epidermis and hair follicle, and both quiescent and intermediate cell states of the basal and infundibulum stem cell populations were distinguished. This study proposed a presorted method to investigate the relationship between integrin expression and epidermal heterogeneity. Multiple epidermal cell types and their expression profiles were identified, which provides data resources for dermatology research. Abstract : Epidermal cells were sorted with differential expression of α6 and β1 integrins to explore epidermal heterogeneity. Using bulk‐cell RNA‐seq, nine cell populations sorted were identified as the main cell types in epidermis. Using single‐cell RNA‐seq, 576 single cells were sorted from re‐epithelialized wounds and identified 13 epidermal cell populations.